Acute kidney injury post-abdominal surgery in infants: implications for prevention and management - Duong, Minh Dien; Kwak, Silvia; Bagrodia, Naina; Basalely, Abby (Frontiers in Pediatrics, 2023)
Acute kidney injury (AKI) is common in critically ill infants and is associated with long-term sequelae including hypertension and chronic kidney disease. The etiology of AKI in infants is multifactorial. There is robust literature highlighting the risk of AKI after cardiothoracic surgery in infants. However, risk factors and outcomes for AKI in infants after abdominal surgery remains limited. This article reviews the epidemiology and association of abdominal surgery with postoperative AKI and suggests methods for AKI management and prevention. Postoperative AKI may result from hemodynamic shifts, hypoxia, exposure to nephrotoxic medications, and inflammation. Infants in the intensive care unit after intraabdominal surgeries have a unique set of risk factors that predispose them to AKI development. Prematurity, sepsis, prolonged operation time, emergent nature of the procedure, and diagnosis of necrotizing enterocolitis increase risk of AKI after intrabdominal surgeries. Prevention, early diagnosis, and management of AKI post-abdominal surgery is imperative to clinical practice. Close monitoring of urine output, serum creatinine, and fluid status is necessary in infants after abdominal surgery. A recent study suggests elevated levels of a urinary biomarker, neutrophil gelatinase-associated lipocalin (NGAL), 24 h after an abdominal procedure may improve early prediction of AKI. Identification of risk factors, avoidance of nephrotoxic medications, careful fluid balance, early detection of AKI, and maintenance of hemodynamic stability is imperative to potentially prevent and/or mitigate AKI.